2002
DOI: 10.1136/bjo.86.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin treatment for hyperlacrimation secondary to aberrant regenerated seventh nerve palsy or salivary gland transplantation

Abstract: Aim: To investigate the potential of botulinum toxin A for treating hyperlacrimation. Methods: Three patients with unilateral symptoms of hyperlacrimation (diagnosed as "crocodile tearing") and one patient with a submandibular salivary gland transplant (SMGT) were studied. Tear production was quantified in the resting and stimulated (chewing or following exercise) state, using Schirmer's test and tear clearance. Lacrimal scintigraphy was used to assess outflow. Intraglandular injections (for patients with "cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 12 publications
0
46
0
6
Order By: Relevance
“…Uma razão que poderia explicar os resultados encontrados no teste de BUT e de Schirmer é o fato de que a toxina botulínica pode ter um efeito farmacológico direto na produção de lágrima pela glândula lacrimal quando aplicada intraglandular, e com menor eficácia via subcutânea (10)(11) . A toxina botulínica tipo A afeta a transmissão colinérgica durante as manifestações sistêmicas do botulismo.…”
Section: Discussionunclassified
“…Uma razão que poderia explicar os resultados encontrados no teste de BUT e de Schirmer é o fato de que a toxina botulínica pode ter um efeito farmacológico direto na produção de lágrima pela glândula lacrimal quando aplicada intraglandular, e com menor eficácia via subcutânea (10)(11) . A toxina botulínica tipo A afeta a transmissão colinérgica durante as manifestações sistêmicas do botulismo.…”
Section: Discussionunclassified
“…7,8 The effect of botulinum toxin can last 3-4 months. 7 Although Boroojerdi et al 8 reported only focal side effects of Figure 2 Increase in ptosis and narrowing of the palpebral aperture on the affected side during cheek puffing.…”
Section: Discussionmentioning
confidence: 99%
“…Es existieren 2 Injektionsverfahren: zum einen kann transkutan in mehreren Depots die Tränendrü-se behandelt werden [16,19], bei der anderen Technik erfolgt die Injektion transkonjunktival [1], wobei der Patient gebeten wird, mit dem behandelten Auge zur Nasenspitze zu blicken. Bereits mit recht niedrigen Dosierungen von 2,5 Einheiten Botox®, Fa.…”
Section: Behandlungsschemataunclassified